β-Cell Autophagy Pathway and Endoplasmic Reticulum Stress Regulating-Role of Liposomal Curcumin in Experimental Diabetes Mellitus: A Molecular and Morphometric Study - Safaa I. Khater; Mohamed F. Dowidar; Aya E. Abdel-Aziz; Tarek Khamis; Naief Dahran; Leena S. Alqahtani; Mohamed M. M. Metwally; Al-Sayed Al-Hady Abd-Elrahamn; Mohammed Alsieni; Manal E. Alosaimi; Maram H. Abduljabbar; Amany Abdel-Rahman Mohamed (Antioxidants, 2022)
Background: Autophagy can confer protection to pancreatic β-cells from the harmful effects of metabolic stress by delaying apoptosis. Curcumin (CUR) alleviates oxidative and endoplasmic reticulum (ER) stress, activates autophagy, reduces inflammation, and decreases β-cell damage in type I diabetes. Liposomal CUR (LPs-CUR) has a higher therapeutic value and better pharmacokinetics than CUR. Objectives: We determined LPs-CUR’s ability to alleviate stress, reduce β-cell damage and unraveled the mechanism underlying its protective effect using a streptozotocin (STZ)-induced type I diabetic rat model. Methods: Sprague–Dawley rats were grouped into vehicle control, STZ-diabetic (STZ 65 mg/kg), STZ-diabetic-3-MA (3-methyladenine [3-MA] 10 mg/kg b.wt), STZ. diabetic-LPs-CUR (LPs-CUR 10 mg/kg b.wt), and STZ diabetic-LPs-CUR-3-MA (LPs-CUR 10 mg/kg b.wt; 3-MA 10 mg/kg b.wt). Results: LPs-CUR significantly reduced blood glucose, oxidative stress, and cellular inflammation in the pancreatic tissue (p < 0.001). ER stress-dependent genes included ATF-6, eIF-2, CHOP, JNK, BiP, and XBP LPs-CUR significantly suppressed fold changes, while it upregulated the autophagic markers Beclin-1 and LC3-II. Conclusions: LP-CUR ameliorates β-cell damage by targeting the autophagy pathway with the regulatory miRNAs miR-137 and miR-29b, which functionally abrogates ER stress in β-cells. This study presents a new therapeutic target for managing type I diabetes using miR-137 and miR-29b.